1997
DOI: 10.1046/j.1365-2249.1997.4031299.x
|View full text |Cite
|
Sign up to set email alerts
|

IL-5 expressed by CD4+ lymphocytes from Echinococcus multilocularis-infected patients

Abstract: SUMMARYIL-5 is a major factor inducing differentiation of B lymphocytes into immunoglobulin-producing cells as well as a main regulator of eosinophils. Recently, we have shown that peripheral blood mononuclear cells (PBMC) from patients with alveolar echinococcosis (AE) express IL-5 mRNA after stimulation with crude Echinococcus multilocularis (E.m.) antigen. To characterize the observed response in lymphocyte subpopulations, we cultured patients' PBMC in the presence of E.m. crude antigen for 18 h. PBMC were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
(36 reference statements)
4
16
1
Order By: Relevance
“…As no major differences were observed in the present study, the differences in the cytokine response of both types of patients could not be explained by variations in their mitotic responsiveness to antigenic stimulation. IL-5 has been shown to be specifically stimulated by E. multilocularis antigens in progressive AE [8,9]. In this study, mRNA semiquantification showed that there was no significant difference in IL-5 mRNA expression between subjects with an efficient immune response against the parasite and patients who developed progressive AE.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…As no major differences were observed in the present study, the differences in the cytokine response of both types of patients could not be explained by variations in their mitotic responsiveness to antigenic stimulation. IL-5 has been shown to be specifically stimulated by E. multilocularis antigens in progressive AE [8,9]. In this study, mRNA semiquantification showed that there was no significant difference in IL-5 mRNA expression between subjects with an efficient immune response against the parasite and patients who developed progressive AE.…”
Section: Discussionmentioning
confidence: 59%
“…The higher increase in IL‐5 production observed in patients with progressive AE could be enhanced by a particular genetic background; the increase seems to be the consequence of an expanding IL‐5‐secreting cell population: we [10] and Jenne et al . [9] demonstrated that this secretion of IL‐5 was restricted to CD4 + T lymphocytes in human AE. Echinococcus multilocularis antigenic preparations could regulate the expression of IL‐5 gene at the post‐transcriptional level, as suggested by the results of IL‐5 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…In many chronic infections the clinical outcome of the disease is associated with Th1 or Th2 cell activation. In most helminthic infections the healing or protection is related to Th2 cell activation [13][14][15], even if some infections, including trichinellosis, schistosomiasis, and cystic and alveolar echinococcosis, display Th2-mediated susceptibility [6,7,[16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The complex immune response during infection is characterized by an abnormal production of various interleukins, such as interleukin-5 [19,20], IL-27 [21], high levels of IL-10 and TGF-beta [18,22]. Simultaneously, insufficient production of IL-12 [23], IL-31, IL-33 [21], IFN-gamma and cytotoxic T cells leads to an enhanced tolerance towards the parasite.…”
Section: Introductionmentioning
confidence: 99%